Kinetic studies on the reactions of different bifunctional platinum(II) complexes with selected nucleophiles - Bogojeski, Jovana; Bugarĉić, Ẑivadin D.; Puchta, Ralph; van Eldik, Rudi (European Journal of Inorganic Chemistry, 2010)
Substitution reactions of the complexes cis-[Pt(NH3) 2Cl2], [Pt(SMC)Cl2]-, [Pt(en)Cl 2], and [Pt(dach)Cl2], where SMC = S-methyl-L-cysteine, en = ethylenediamine and dach = 1,2-diaminocyclohexane, with selected biologically important ligands, viz. guanosine-5′-monophosphate (5′-GMP), L-histidine and 1,2,4-triazole, were studied. All reactions were studied in aqueous 25 mM Hepes buffer in the presence of 5 mM NaCl at pH = 7.2 under pseudo-first-order conditions as a function of concentration at 310 K by using UV/Vis spectrophotometry. Two consecutive reaction steps, which both depend on the nucleophile concentration, were observed in all cases. The second-order rate constants for both reaction steps indicate a decrease in the order [Pt(SMC)Cl2]- > cis-[Pt(NH3) 2Cl2] > [Pt(en)Cl2] > [Pt(dach)Cl 2]. DFT calculations (B3LYP/LANL2DZp) showed that the Pt-N7(Guo) adduct is more stable than the Pt-S(thioether) adduct for the studied complexes cis-[Pt(NH3)2Cl2], [Pt(SMC)Cl2] -, and [Pt(en)Cl2]. The calculations collectively support the experimentally observed substitution of thioethers bound to PtII complexes by N7(5′-GMP). Finally, this result could be the first to clearly show how much the Pt-N7(Gua) adduct is more stable than the Pt-S(thioether).Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Computational chemistry; Kinetics; Ligand effects; Platinum; Reaction mechanisms